TRENDS FOR UKRAINE’S CURRENCY MARKET DEVELOPMENT - Dernova I. А.; Zdir V.A.; Piskova S.P. (Scientific Journal of Pedagogy and Economics, 2020)
At the current stage of the country’s economic development, its foreign exchange market is determined by the complicated economic relations associated with foreign currency buying and selling for servicing transactions in the sphere of trade and business. Growing openness of the national economy and Ukraine’s integration into the world economic system are among the reasons for the increased influence of external and internal factors in the foreign exchange market, increased volatility of the national currency exchange rate and pose high risk on the transactions in the foreign exchange market. This, in turn, diminishes the attractiveness of the economy for doing business. Combining the national economy with the world market through the mechanism of monetary relations, the exchange rate of the national currency is tightly linked to all economic processes. On the one hand, it is affected by a complex set of endogenous and exogenous macroeconomic factors; on the other hand, it affects the country’s financial situation. National currency depends on the competitiveness of domestic production in international markets, volume and direction of foreign economic relations, and cash flows. In this context, the hryvnia exchange rate is seen as an important indicator of the country’s economic development, an effective monetary policy instrument of the Central Bank, and a key characteristic of the currency market. A strong need to improve the efficiency of the currency market in Ukraine encouraged the choice of the research topic. The purpose of the study is to determine the peculiarities of the situation on the national currency market and outline the trends for changes of the main indicators of its activity. Particular attention is paid to the analysis of tendencies of the hryvnia exchange rate fluctuation against the US dollar and euro, as well as the factors that cause volatility of the Ukrainian currency market. The study identifies the peculiarities of Ukraine’s currency market during 2015-2019. Based on the analysis of the dynamics of the hryvnia exchange rate, the main stages of the exchange rate change have been pointed out and the determining factors of the change of the hryvnia exchange rate against the US dollar and euro have been highlighted at each stage. The situation on the national currency market and the main indicators, which testify to the effectiveness of its functioning, have been evaluated. The dynamics of Ukraine’s foreign exchange reserves, currency interventions of the National Bank of Ukraine and gross external debt have been investigated. Methods of correlation analysis have been used to identify exchange rate factors. Synchronization of dynamics of individual macroeconomic indicators and hryvnia exchange rates against the US dollar and euro during the period of 2015 and 11 months of 2019 has been explored. According to the data obtained, assumptions about the future trends of the national currency market have been made.